Persepsi Pasien tentang Kualitas Pelayanan Rumah Sakit pada Masa Pandemi Covid-19 - Riska Yanuarti; Henni Febriawati; Wulan Angraini; Bintang Agustina Pratiwi; Nopia Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the patient's perception of the quality of service at the Harapan and Doa Hospital in Bengkulu City during the Covid-19 pandemic. The research design used was quantitative using a cross-sectional design. Overall, the results showed that the patient's perception of the five dimensions of service quality was still not good, namely 57.1% reliability, 63.8% responsiveness, 56.2% assurance, 50.5% empathy, and 55.2% physical evidence. The results of the chi-square test showed that there was a significant effect between age (p-value = 0.001) , gender (p-value = 0.001), education (p-value = 0.001), occupation (p-value = 0.001) on patients' perceptions of quality. service. In conclusion, most of the respondents stated that the Outpatient Polyclinic of Harapan and Doa Hospital Bengkulu City was still not good. There was an influence of age, gender, education, and occupation on patients' perceptions of service quality. Keywords: Satisfaction, Quality, Pandemic, Perception